REKONSTRUKSI PENDIDIKAN ISLAM (Studi Kritis Filsafat Pendidikan Islam Muhammad Iqbal) - Muchamad Agus Munir (Islamic University of Indonesia, 2017)
The problems of Islamic education in Indonesia has been so far related to the dichotomy of knowledge resulting in the formation of the mindset in society that considers the graduates of public education are more advanced and successful, while graduates of Islamic education only become religious propagators and are less reliable in the workplace. Islamic education is not seen as an integral part in nation-building. Therefore, certain ideas are required to solve these problems. One of the great ideas was expressed by Muhammad Iqbal; that education is not a stagnant system, but rather an ongoing process and affected by the times. Iqbal proposed his ideas on education with reference to his thoughts about man; that man has the power to be free without any pressure. Thus, Islamic education desired by Iqbal is a dynamic and contextual Islamic education.Keyword: reconstruction, Islamic education, Muhammad Iqbal